Melatonin ameliorates cognitive deficits through improving mitophagy in a mouse model of Alzheimer's disease. Issue 4 (15th October 2021) - Chen, Chongyang; Yang, Chao; Wang, Jing; Huang, Xi; Yu, Haitao; Li, Shangming; Li, Shupeng; Zhang, Zaijun; Liu, Jianjun; Yang, Xifei; Liu, Gong‐Ping
Abstract: While melatonin is known to have protective effects in mitochondria‐related diseases, aging, and neurodegenerative disorders, there is poor understanding of the effects of melatonin treatment on mitophagy in Alzheimer's disease (AD). We used proteomic analysis to investigate the effects and underlying molecular mechanisms of oral melatonin treatment on mitophagy in the hippocampus of 4‐month‐old wild‐type mice versus age‐matched 5 × FAD mice, an animal model of AD. 5 × FAD mice showed disordered mitophagy and mitochondrial dysfunction as revealed by increased mtDNA, mitochondrial marker proteins and MDA production, decreased electron transport chain proteins and ATP levels, and co‐localization of Lamp1 and Tomm20. Melatonin treatment reversed the abnormal expression of proteins in the signaling pathway of lysosomes, pathologic phagocytosis of microglia, and mitochondrial energy metabolism. Moreover, melatonin restored mitophagy by improving mitophagosome–lysosome fusion via Mcoln1, and thus, ameliorated mitochondrial functions, attenuated Aβ pathology, and improved cognition. Concurrent treatment with chloroquine and melatonin blocked the positive behavioral and biochemical effects of administration with melatonin alone. Taken in concert, these results suggest that melatonin reduces AD‐related deficits in mitophagy such that the drug should be considered as a therapeutic candidate for the treatment of AD.